Thse Security Implications of Language Policy in Multilingual Nations - Timothy Ameh (Journal of Social Research, 2024)
This study examines the security implications of language policy in multilingual nations, focusing on its role in fostering inclusion, managing diversity, and mitigating conflict. Through case studies of Nigeria, India, and Switzerland, the research highlights how language policies influence national identity, governance, and socio-economic equity. In Nigeria, the dominance of English marginalizes indigenous languages, exacerbating ethnic tensions and socio-economic disparities. India’s federal structure accommodates linguistic diversity but continues to face challenges with regional resistance to Hindi dominance. Switzerland, by contrast, exemplifies the success of inclusive multilingual policies in maintaining stability and fostering unity. Drawing on theoretical frameworks such as Critical Language Policy, Linguistic Justice, and Intersectionality, the study underscores the importance of equitable and participatory approaches to language planning. It concludes that inclusive language policies reduce grievances, promote cohesion, and enhance national security, while exclusionary practices risk alienation and conflict. The findings contribute to the growing discourse on the nexus between language, governance, and security, offering valuable insights for policymakers in linguistically diverse nations.